Competitive Advantages Micro, Small And Medium Enterprises (SMES) In Internasional: Systematic Literature Review - Rifaul Kirom, Novita; Sudarmiatin, Sudarmiatin; Sumarsono, Hadi (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
Competitive Advantage is outcome of the planned strategy business, in the sector micro, small or medium. Direction strategic embodied through ability produce profit more big from competitors. Many factors are the same importance in produce Power competitive. Some of them is strategic factors, development source Power people , knowledge management and roles Information & Communication Technology (ICT). Factors of the wiIl create and mantain superior position from competitor, the so-called superiority competitive. However, understanding thorough about state-of-art from superiority competitive Still needed. because it article This aim For classif, identify pubIications scientific and do analysis thematic to literature latest To use create extensive and detailed understanding in the field superiority competitive. Method study done with method of systematic Mapping study (SMS) for study publication scientific in the field superiority competitive advantage on focus or research type from time until time. Research results This produce categorization and quantification studies superiority competitive in various dimensions as weII as overview topics and trends study moment this.